Polityczne, kulturowe i społeczne czynniki przemian rynku książki dziecięcej w Polsce na przykładzie wydawnictwa Nasza Księgarnia - Hojka, Bożena; Jamróz-Stolarska, Elżbieta (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Poland’s turbulent history, marked by several changes in the political system, has combined with dynamic economic, social, and cultural factors to profoundly affect the operations of all industries, including the publishing sector. This paper outlines the development of Nasza Księgarnia (literally: Our Bookshop), a publishing house founded in 1921 whose one-century- long history perfectly embodies the profound transformations which the Polish market of children’s and young adults’ books has experienced from the moment Poland regained sovereign statehood in 1918, through the communist period and the political transition of 1989, to the beginning of the new millennium. The argument is theoretically underpinned by the framework proposed by Michael Bhaskar (Bhaskar 2013), and the operations of Nasza Księgarnia are examined in terms of its crucial notions of framing, filtering, and amplification. At the same time, Hans Heino-Ewers’s (Heino-Ewers 2009) model of children’s literary communication is applied to highlight the specific role of Nasza Księgarnia as a publisher for children and young adults. These two theoretical tools offer insight into the ways in which political and social changes affected the evolution of the publishing repertoire and the editorial form of the children’s book in Poland throughout and at the turn of the 20th century.